100 brain-friendly lessons for unforgettable teaching and learning (9-12) - Tate, Marcia L. (Corwin, 2020)
"Unless there is job-embedded follow-up to any professional learning experience or workshop, very little change in teacher behavior takes place. However, there is very little time during Marcia's workshops for teachers to develop their own brain-compatible lessons using the lesson template she provides. The purpose of these books would be to provide just that--an opportunity for teachers to see multiple examples of cross-curricular lessons which they could immediately replicate in their own classrooms or to begin to develop plans of their own. This book will enable high school teachers to design and implement lessons that take advantage of the way that all student brains learn. It would be cross-curricular with 25 sample lessons included in each of the four major content areas: English/language arts, mathematics, science, and social studies. The most frequently-taught objectives contained in national and international curricula would be delineated and the lessons designed would be around them"--